Six years of car driving experience: impact of psychological status, sleep, fatigue and quality of life in female drivers in Saudi Arabia: an online survey study - Thamir Al-khlaiwi; Dena S. Alsuhaibani; Hoor K. Aloraini; Jana I. Alhazmi; Razan A. Almohanna; Sara A. Alsheikh; Turkia A. Alsheik; Norah Alrashoud; Muhammad Iqbal (BMC Public Health)
Abstract Background In 2018, Saudi women were legally allowed to drive and obtain driver’s licenses for the first time—an important milestone that aligns with the goals of Saudi Vision 2030. The aim of our study was to evaluate the driving experience of women in Saudi Arabia in relation to depression, anxiety, stress, sleep, fatigue, and quality of life. Methods This comparative cross-sectional study was conducted using an online questionnaire, distributed to female drivers and non-drivers residing in Saudi Arabia between November 2024 and March 2025. The questionnaires were distributed via social media platforms and through personal outreach efforts. The online survey consists of five sections: (1) Sociodemographic characteristics, knowledge regarding driving, insurance, and work location. (2) We used Depression, Anxiety, and Stress Scale 21 (DASS-21) which was a validated 21-item Arabic self-report survey assessing depression, anxiety, and stress. 3) Sleep was assessed by using Pittsburgh Sleep Quality Index (PSQI). 4. Fatigue was evaluated by Fatigue Severity Scale (FSS). 5. A 12-item Quality of Life Questionnaire was used to evaluate quality of life. Results A total of 1,382 women residing in Saudi Arabia enrolled in the study and completed the questionnaire. There were no statistically significant differences between drivers and non-drivers across all measured domains, including mental health (40.10 ± 7.82, 40.23 ± 8.16, p = 0.764), physical health (36.47 ± 5.40, 36.60 ± 5.92, p = 0.695), sleep quality (7.10 ± 3.48, 6.95 ± 3.26, p = 0.460), depression (14.10 ± 11.78, 13.45 ± 11.30, p = 0.302), anxiety (12.55 ± 10.82, 12.34 ± 10.66, p = 717), and stress (16.76 ± 11.96, 16.29 ± 17.17, p = 0.476) respectively. Although not statistically significant (p = 0.078), the mean Perceived Fatigue Severity Scale score was higher in women who drive (31.69 ± 14.45) compared to non-drivers (30.35 ± 17.72). Our results indicated moderate levels of anxiety (12.45 ± 10.74), depression (13.80 ± 11.55), sleep disturbances (7.03 ± 3.38), and fatigue (31.09 ± 14.13) in both groups (total sample size), though no statistically significant differences were observed between drivers and non-drivers (p > 0.05). Conclusions This is the first study to examine the six-year driving experience of Saudi women since they were granted the legal right to drive. No significant differences were found in sleep, fatigue, stress, or overall well-being between drivers and passengers. However, longer commutes (over 30 min) were associated with increased anxiety, sleep disturbances, depression, and fatigue. These are preliminary findings, and further research is needed to explore the factors influencing the mental and physical health of Saudi women.